The Effect of Product Quality, Price Promotion and Brand Image on Purchasing Decisions at Somethinc Skincare - Nurvita, Ridha Afni; Saputro, Edy Purwo (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Purchasing decisions are consumers' understanding of the wants and needs of a product by assessing existing sources by setting purchasing goals and identifying alternatives. The purpose of this research is to analyze the influence of product quality, price promotions and brand image on purchasing decisions at Skincare Somethingnc. This research method is quantitative. The data used in this research uses primary data. The data collection method used in this research is by using a questionnaire or questionnaire via online media in the form of a goggle form. The population of this research is all consumers in Surakarta who have purchased and used various skincare products. The sampling technique used in this research is nonprobability sampling with the purposive sampling method. The sample for this research consisted of 100 respondents. The analysis carried out was assisted by using the SPSS version 25 application. The results of this research are that product quality has a positive and significant effect on purchasing decisions. Price promotions have a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions.